HUMAN DESTRUCTIVENESS IN THE EXISTING PRACTICES OF LATE MODERNISM VIOLENCE: POSITIVE AND NEGATIVE DIMENSIONS - Marchenko, O. V.; Martseniuk, L. V. (Anthropological Measurements of Philosophical Research, 2020)
Purpose. Research of the phenomenon of human destructiveness in the context of metaphysical images and violence practices of late Modernism. Theoretical basis. The problem is that the philosophical reflection of violence as objectified, realized destructiveness of man is usually contextual in nature and is on the periphery of understanding its external manifestations. Accordingly, anthropological crisis remains behind the scenes, as evidenced by the devaluation of the humanistic potential of modern culture. That is why one should turn the focus from the obvious, objectively conditioned incarnations of violence in the XXI century (armed conflicts, local wars, terrorist acts) to the internal factors that are in the realm of existential. The departure from the consideration of violence as an abstract, faceless or ideologically colored evil allowed us to focus on man, his way of thinking, life and social orientations, feelings and internal contradictions, which find their expression in one or another form of destructiveness. Originality. Based on the works of M. Scheler and E. Fromm defining for philosophical anthropology and psychoanalysis, for the first time the conceptualization of positive and negative forms of manifestation of human destructiveness against the background of sociocultural transformations of late Modernism was carried out. It has been proved that its ontological principles are rooted in specifically human existence and relations with other members of society, while anthropological ones are directly connected with the endless struggle of the life, the vital with the spirit in man. Conclusions. Violence is a tool and a product of man’s transition to more mature and complex forms of existence. The interdependence of the violence and nonviolence practices ensures the progressive movement of humanity towards society humanization. This progress is accompanied by a natural internal conflict of personality, which can be both progressive and regressive. At the metaphysical level, destructiveness appears as a connection between the entropy of world existence as a whole and the instability of human existence itself, which is a complexly organized and open to the world system. Self-transcendence as an anthropological prerequisite for human destructiveness has a dual nature and combines negative and positive characteristics, the content and significance of which were revealed in the study. The authors are convinced that there is no other way to overcome the negative, malignant destructiveness, except for the incessant, daily gathering of life meanings around them and their development. After all, the loss of such core structures of the existence as the meaning, purpose and value of life has become a truly global problem for the modern world. Emphasis is placed on the need to keep in harmony the trinity of body-soul-spirit, which will allow a person in any social transformation to preserve and increase his integrity.